Prevalence and associated factors of depression among Jimma University students. A cross-sectional study - Gutema Ahmed; Alemayehu Negash; Habtamu Kerebih; Daniel Alemu; Yonas Tesfaye (International Journal of Mental Health Systems, 2020)
Abstract Background Depression is a common health problem among university students. It is debilitating and has a detrimental impact on students psychosocial, emotional, interpersonal functioning and academic performance, However, there is a scarcity of information on this regard in higher education institutions in Ethiopia, so the current study was conducted to assess the prevalence of depression and its associated factors among Jimma University students. Methods An institution-based quantitative cross-sectional study was conducted on a total of 556 sampled students selected by a multistage stratified sampling technique. Beck Depression Inventory (BDI-II) was used to screen depression severity. Data was collected through a pretested, structured, and self-administered questionnaire. The collected data were checked manually for completeness and entered into Epidata manager Version 2.0.8.56 data entry software then exported to SPSS version 20 Statistical software for analysis. The obtained data were described using descriptive statistics as well as logistic regression analysis was done to determine the independent predictors of the outcome variable. First bivariate analysis was done and variables significant at p value ≤ 0.25 were entered into a multivariate logistic regression analysis to control for confounders. The significance of association was determined at a 95% confidence interval and p-value < 0.05. Result The prevalence of depression among the students was 28.2%. Having a mentally ill family member (OR = 2.307, 95%CI 1.055–5.049), being from the college of Social science and humanity (OR = 2.582, 95%CI 1.332–5.008), having sex after drinking (OR = 3.722, 95%CI 1.818–7.619), being hit by sexual partner (OR = 3.132, 95%CI 1.561–6.283), having childhood emotional abuse (OR = 2.167, 95%CI 1.169–4.017), having monthly pocket money between 500-999 ETB (OR = 0.450, 95% CI 0.204–0.995), and promoted academic performance (OR = 2.912, 95% CI 1.063–7.975) were significantly associated with depression. Conclusion The prevalence of depression among Jimma University students was high and positively associated with being from the college of social science and humanity, history of a hit by a sexual partner, having a mentally ill family member, having more monthly pocket money, promoted academic performance, having sex after drinking and childhood emotional abuse. Therefore, establishing depression screening services on the campus and designing proper mental health intervention programs is recommended to tackle the problem.